1997
DOI: 10.1002/(sici)1097-4628(19970523)64:8<1531::aid-app11>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of composition of modified polyamide on barrier properties of polyethylene/modified polyamide blends

Abstract: A systematic study on the effects of types and contents of compatibilizer precursors (CPs) on degrees of crystallinity (W c ), melt shear viscosities ( h s ), and permeation barrier properties of modified polyamides (MPAs) and on their corresponding morphology and barrier properties of bottles blow-molded from polyethylene (PE)/MPA blends is reported. Two alkylcarboxyl-substituted polyolefins were selected as CPs to modify PA and to improve its permeation resistance to xylene by the ''reactive extrusion'' proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 1 publication
2
33
0
Order By: Relevance
“…Formation of CPgrafted-PA copolymers through the reaction of carboxyl groups of CP with the terminal amine groups of PA has been reported during the preparation of MPA. [12,13] The blends of MPA and EVOH (MPAEVOH) were prepared by meltblending of the MPA and EVOH. The dried components of MPA/EVOH at varying weight ratios were then fed into a Fure Shuen 40SP-H single-screw extruder to prepare the MPAEVOH resins.…”
Section: Materials and Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Formation of CPgrafted-PA copolymers through the reaction of carboxyl groups of CP with the terminal amine groups of PA has been reported during the preparation of MPA. [12,13] The blends of MPA and EVOH (MPAEVOH) were prepared by meltblending of the MPA and EVOH. The dried components of MPA/EVOH at varying weight ratios were then fed into a Fure Shuen 40SP-H single-screw extruder to prepare the MPAEVOH resins.…”
Section: Materials and Sample Preparationmentioning
confidence: 99%
“…These interesting gasoline barrier and morphological properties of PE, PE/MPA and PE/MPAEVOH were investigated in Further investigations found that these barrier properties of PE/PA/CP blends depend greatly on the manner of blending and on the resulting morphology. [1][2][3][4][8][9][10][11] Our latest studies [12][13][14][15] indicated that the type and content of CP and PA present in a modified polyamide (MPA) have significant effects on the barrier, morphology and rheological properties of MPA resins and the corresponding PE/ MPA blends. In addition, the melt shear viscosities of polyethylene and modified polyamide were found to exhibit a significant influence on the deformation and morphology of MPA during the blow-molding process of PE/MPA blends.…”
Section: Introductionmentioning
confidence: 99%
“…Formation of CP-grafted-PA copolymers through the reaction of carboxyl groups of CP with the terminal amine groups of PA was reported during the preparation of MPA. 14,15 Each type of MPA pellet prepared from the twin-screw extruder was dried at 80°C for 16 h and then dry-blended with PE at a weight ratio of 90:10. In contrast, each type of MPE pellet was dried at 80°C for 16 h and then dry-blended with PA at various weight ratios (see Table II).…”
Section: Materials and Sample Preparationmentioning
confidence: 99%
“…These products are the basis for further syntheses of block copolymers and functional polymers. In addition, the coupling of polyamides with polyolefins as compatilizers should be mentioned [85]. The production of block copolymers by a selective transesterification reaction [86] and the defined in situ compatibilization of polypropylene polybutylene-terephthalate blends [80] emphasize the possibilities opening up in this area of chemical technology.…”
Section: Reaction In the Melt -Reactive Extrusionmentioning
confidence: 99%